Measuring Police-Community Interaction Variables in Indianapolis, 1999-2000 - Duffee, David E. ([Verlag nicht ermittelbar], 2007)
This study, funded under the Measuring What Matters Program, was conducted to identify general neighborhood strengthening, or community building, processes and police contributions to them. The purpose of the study, also known as the Police-Community Interaction Project (PCIP), was to conceive, identify, or define recognizable patterns of interaction and to find ways to treat these as quantities that vary in amount and can be shown to fluctuate over time or across places. To that end, researchers conducted surveys of block clubs, neighborhood associations, and umbrella groups to gauge the issues that were important to them, steps they were taking to address these issues, and the ways in which they interacted with the police. Researchers also attended the meetings and events held by the Westside Cooperative Organization (WESCO), an umbrella group, and gathered coded data about the meetings, events and issues discussed. Specific variables in the study include demographic variables about the blocks, neighborhoods, and districts represented by the organizations, descriptive variables on the organizations themselves, variables describing issues of importance to the organizations and steps those organizations were taking to address the issues, variables to describe the interaction between the organizations and police, and variables describing police involvement in community activities.